Management of Ellis Class II Fracture in Young Permanent Maxillary Central Incisor - Rabiatul Adawiyah; Jeffrey (Denta Journal Kedokteran Gigi, 2024)
Background: Tooth fracture is a condition of missing or lost fragments of a complete tooth. Tooth fracture usually occurs simultaneously with another oral injury. Objective: This case report discussed the management of Ellis class II fractures on an immature permanent central incisor of a patient who reported to Jenderal Achmad Yani University (Unjani) Dental Hospital. Case: An 11-year-old girl revealed a broken upper left tooth, sensitive to cold drinks that interfered with her appearance one year ago. The patient had a good general condition, no abnormalities during an extraoral examination, and a history of pain on the lower back tooth since a year ago. Case Management: Management of Ellis class II fracture in young permanent central incisor was conducted by using a class IV composite resin restoration. Conclusion: The management of Ellis class II fracture should be conducted holistically and systematically with subjective, intraoral, extraoral, and adjunctive examinations which should be performed correctly and considering the child’s psychology.